Obtaining Sulfur from Sulfur Hexafluoride and Studying the Sulfur Isotopes Properties by Using Vibrational Spectroscopy; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Egorov N. B. Nikolai Borisovich (2015, 2015)
Title screen